2023
DOI: 10.1186/s12934-023-02213-z
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor GCN4 contributes to maintaining intracellular amino acid contents under nitrogen-limiting conditions in the mushroom Ganoderma lucidum

Lingdan Lian,
Jinjin Qiao,
Xiaoyu Guo
et al.

Abstract: Background Edible mushrooms are delicious in flavour and rich in high-quality protein and amino acids required by humans. A transcription factor, general control nonderepressible 4 (GCN4), can regulate the expression of genes involved in amino acid metabolism in yeast and mammals. A previous study revealed that GCN4 plays a pivotal role in nitrogen utilization and growth in Ganoderma lucidum. However, its regulation is nearly unknown in mushrooms. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Edible and medicinal fungi are rich in the high-quality proteins and amino acids required by humans, and their content and composition are important indicators for evaluating the nutrition and flavor of edible and medicinal fungi. Lian et al [177] silenced the alkaline leucine-transcription-factor-coding gene Gcn4 in G. lucidum and reported that the amino acid content of the mutant strain was reduced by 54.2-88.3% compared with the wild type. They hypothesized that GCN4 could modulate the expression of amino-acid-related synthesis genes and transporter genes, providing precursors for amino acid biosynthesis by enhancing the TCA cycle and glycolytic pathway.…”
Section: Research Progress On Genes Related To Substrate Utilization ...mentioning
confidence: 99%
“…Edible and medicinal fungi are rich in the high-quality proteins and amino acids required by humans, and their content and composition are important indicators for evaluating the nutrition and flavor of edible and medicinal fungi. Lian et al [177] silenced the alkaline leucine-transcription-factor-coding gene Gcn4 in G. lucidum and reported that the amino acid content of the mutant strain was reduced by 54.2-88.3% compared with the wild type. They hypothesized that GCN4 could modulate the expression of amino-acid-related synthesis genes and transporter genes, providing precursors for amino acid biosynthesis by enhancing the TCA cycle and glycolytic pathway.…”
Section: Research Progress On Genes Related To Substrate Utilization ...mentioning
confidence: 99%